2015
DOI: 10.1002/2015jd023254
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol transport over the Andes from the Amazon Basin to the remote Pacific Ocean: A multiyear CALIOP assessment

Abstract: Six years (2007Six years ( -2012 of data from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) satellite instrument were used to investigate the vertical distribution and transport of aerosols over the tropical South American continent and the southeast Pacific Ocean. The multiyear aerosol extinction assessment indicates that aerosols, mainly biomass burning particles emitted during the dry season in the Amazon Basin, are lifted in significant amounts over the Andes. The aerosols are mainly transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 69 publications
1
43
0
1
Order By: Relevance
“…Although their emission is much smaller than marine and dust aerosols, smoke particles contribute at least 10 % of the FT AOD. This can partly be explained by the location of the emission sources (near the convective regions) and aerosol properties such as hygroscopicity, which is likely lower for smoke than sulfate-containing pollution (e.g., Carrico et al, 2010). Sea salt particles are hydrophilic and efficient cloud condensation nuclei.…”
Section: Daytime Analysismentioning
confidence: 99%
“…Although their emission is much smaller than marine and dust aerosols, smoke particles contribute at least 10 % of the FT AOD. This can partly be explained by the location of the emission sources (near the convective regions) and aerosol properties such as hygroscopicity, which is likely lower for smoke than sulfate-containing pollution (e.g., Carrico et al, 2010). Sea salt particles are hydrophilic and efficient cloud condensation nuclei.…”
Section: Daytime Analysismentioning
confidence: 99%
“…biomass burning injection height, deposition and BL mixing have also been reported as important (Kipling et al, 2016;Peers et al, 2016). In addition, pyro-convection and orographic lifting are two regional processes that can transport aerosols from the surface to the FT (e.g., Fromm et al, 2006;Yumimoto et al, 2009;Bourgeois et al, 2015). Although Veira et al (2015) showed that only a small fraction (4-5%) of biomass burning plumes reaches the FT, Devasthale and Thomas (2011) indicated that smoke plumes are frequently found above clouds over the ocean near intense biomass burning regions.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates driving processes are common throughout. The aerosol vertical profile is approximately vertical from the surface to a height of: 2.25 km (Huang et al, 2015; Table 2 therein), ~1.5 km (Bourgeois et al, 2015; Fig. 6 therein), ~2 km (Baars et al, 2012; Fig.…”
Section: Drivers Of the Pollutant Vertical Distributionmentioning
confidence: 98%
“…This is important for understanding how mixing, advection and removal affect pollutants differently. Likewise, recent lidar remote sensing from satellite (Bourgeois et al, 2015;Huang et al, 2015) and surface (Baars et al, 2012) platforms do not provide the comprehensive dataset best suited to examining the drivers of multi-pollutant vertical distribution.…”
Section: Introductionmentioning
confidence: 99%